Pengembangan Bahan Ajar Pengantar Pendidikan di Fakultas Keguruan dan Ilmu Pendidikan Universitas Batanghari Jambi - Buyung Buyung (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research aims to develop educational introductory teaching materials. The research method used is reaseach and development (R&D). The teaching material development model used is the Dick and Carey model. This research was conducted at the Faculty of Teacher Training and Education at the even semester 2018/2019. Retrieval of data using questionnaires, interviews and observations. The results of the study based on validation by experts were categorized as feasible with a feasibility percentage for design validation 87%, media validation 90.4% and material experts 87.7%. Followed by a one to one trial with a score of 93.3%. In the small group trial with a score of 92.3%. Then in the field trial trials (group field) with a score of 87.5%. From the results of the Validation and the trials conducted, it can be concluded that the teaching and learning materials are feasible to use.